PEMASARAN KOMODITAS TERIPANG (Holothuroidea) DI KECAMATAN TANIMBAR SELATAN KABUPATEN MALUKU TENGGARA BARAT - Sangaji, Janer (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2024)
Sea cucumbers are a delicious food that is favored by the Chinese community and holds high economic value in the market. They are also traded in dried or preserved forms. According to the Fisheries and Marine Database study, various economically valuable species of sea cucumbers have been identified in the West Southeast Maluku Regency, such as Holothuria scrabra, Holothuria fuscogilva, Holothuria edulis, Telenota ananas, Telenota anax, and Tripeneustes gratilla. This research aims to examine the marketing channels and the factors influencing the production of sea cucumber commodities. The results of the study indicate that: 1) the marketing channel for sea cucumber commodities in Tanimbar Selatan District operates as a one-level marketing system. The marketing functions performed by various marketing entities are as follows: producers carry out six marketing functions, local collectors perform all eight marketing functions, and processing enterprises undertake seven marketing functions. The marketing map illustrates that the distribution of sea cucumber commodities occurs in Tanimbar Selatan, involving producers and local collectors, and extends to inter-provincial regions involving local traders and processing enterprises. 2) the total marketing cost for sea cucumber commodities is IDR 22.860,546 for a single marketing period. The marketing entity incurring the highest cost is local collectors (73.51%), followed by consumers (25.83%), and producers (0.65%). Moreover, the marketing margin for sea cucumbers is IDR 32.164/kg. From this margin and the costs incurred, the average profit at the producer level is IDR 214.397/kg, while the average profit at the local collector level is IDR 29.241/kg. 3) simultaneously, the factors of the fishing season, education, price, and transportation costs significantly impact the production volume of sea cucumbers. However, when analyzed separately, only the fishing season factor significantly affects the production volume, while the other three factors do not have a substantial impact.